Redescription of the type specimens for the Late Jurassic rhynchocephalian Opisthias rarus and a new specimen of Theretairus antiquus from Quarry 9, Morrison Formation, Wyoming, USA - JORGE A. HERRERA-FLORES; THOMAS L. STUBBS; FRANCISCO SOUR-TOVAR (Acta Palaeontologica Polonica, 2022)
We reexamine and redescribe the type specimens and other associated material of the Late Jurassic rhynchocephalian Opisthias rarus, from Quarry 9 of the Morrison Formation. We rediscover and describe a fragment of rock matrix belonging to the holotype that is presented for the first time, and we also comment on undescribed material from Quarry 9 that possibly belongs to an unnamed species of Opisthias. In addition, we describe a new specimen of Theretairus antiquus that helps to reject its proposed status as a junior synonym of O. rarus, and contributes to increase the knowledge of the microvertebrate fauna of the Late Jurassic of North America.